Role of multidrug resistance-associated protein 1 expression in the in vitro susceptibility of rat nerve cell to unconjugated bilirubin - Falcao, A. S. (2015)
Nerve cell injury by unconjugated bilirubin (ILICB) has been implicated in brain damage during neonatal hyperbilirubinemia, particularly in the preterm newborn. Recently, it was shown that UCB is a substrate for the multidrug resistance-associated protein